ANT 2000/01: AWI airborne Radio-Echo Sounding data over the EPICA DML ice core site and western DML extquotesingles Grounding Line and ice shelf (EPICA, SEAL, and VISA projects) - Wilfried Jokat; Heinrich Miller; Uwe Nixdorf; Veit Helm; Daniel Steinhage (PANGAEA, 2025)
This dataset contains airborne radar data acquired using the AWI EMR system during the Antarctic season of 2000/01. The profiles extend across the western Dronning Maud Land along the grounding line, over the Jutulstraumen Glacier, and over the EDML ice core site. The data are available as netCDF files (including waveforms and metadata), KML files of the profile line locations, and quicklook images of the radargrams.